Analysis of Market Reactions Before and During Geopolitical Issues in Europe - Deilamy Nigel Luntungan; Lidia Mawikere; Syermi Mintalangi (E-Jurnal Akuntansi, 2024)
Various events that occur in the world have an impact on the capital market. One such event is the geopolitical events of the Russian invasion of Ukraine on February 24, 2022. The purpose of this study is to determine the influence of geopolitical dynamics in Europe on the market capitalization of energy sector companies. The observation period was carried out at 1 quarter before the event and 3 quarters during the event. This type of research is quantitative research with a descriptive approach. The sampling method used was purposive sampling of 52 companies that were sampled. Data analysis in the form of Wilcoxon Sign Rank difference test using IBM SPSS 26. The result of this study is the occurrence of significant differences in market capitalization in 2 periods before and during geopolitical issues in Europe, and there were no significant differences in market capitalization in 1 period during geopolitical issues in Europe.